Critical care 24 × 7: But, why is critical nutrition interrupted? - Ramakrishnan, Nagarajan (Medknow Publications & Media Pvt Ltd, 2014)
BACKGROUND AND AIMS: Adequate nutritional support is crucial in prevention and treatment of malnutrition in critically ill-patients. Despite the intention to provide appropriate enteral nutrition (EN), meeting the full nutritional requirements can be a challenge due to interruptions. This study was undertaken to determine the cause and duration of interruptions in EN. MATERIALS AND METHODS: Patients admitted to a multidisciplinary critical care unit (CCU) of a tertiary care hospital from September 2010 to January 2011 and who received EN for a period >24 h were included in this observational, prospective study. A total of 327 patients were included, for a total of 857 patient-days. Reasons and duration of EN interruptions were recorded and categorized under four groups-procedures inside CCU, procedures outside CCU, gastrointestinal (GI) symptoms and others. RESULTS: Procedure inside CCU accounted for 55.9% of the interruptions while GI symptoms for 24.2%. Although it is commonly perceived that procedures outside CCU are the most common reason for interruption, this contributed only to 18.4% individually; ventilation-related procedures were the most frequent cause (40.25%), followed by nasogastric tube aspirations (15.28%). Although GI bleed is often considered a reason to hold enteral feed, it was one of the least common reasons (1%) in our study. Interruption of 2-6 h was more frequent (43%) and most of this (67.1%) was related to “procedures inside CCU”. CONCLUSION: Awareness of reasons for EN interruptions will aid to modify protocol and minimize interruptions during procedures in CCU to reach nutrition goals.